Persistent left superior vena cava: Two case reports and a review from nephrologists' perspective. Issue 3 (3rd February 2016) - Sahutoglu, Tuncay; Sakaci, Tamer; Kara, Ekrem; Ahbap, Elbis; Basturk, Taner; Koc, Yener; Sevinc, Mustafa; Akgol, Cuneyt; Kayarlar, Arzu Ozdemir; Ucar, Zuhal Atan; Caglayan, Feyza Bayraktar; Hasbal, Nuri Baris; et al.
Abstract: Thoracic venous anomalies without congenital heart anomalies are present in minority of the population, but they are frequent enough to be encountered while placing hemodialysis catheters through the jugular or subclavian veins. Persistent left superior vena cava is the most commonly seen anomaly and it is rarely noticed before the observation of an unusual course of hemodialysis catheter or guidewire on chest X‐ray. We present two patients with previously unspotted persistent left superior vena cava and uncomplicated hemodialysis catheter insertions through the internal jugular veins with good catheter functions. Review of the relevant literature from a nephrologists' perspective with technical aspects is provided.